2015
DOI: 10.1021/acs.joc.5b01299
|View full text |Cite
|
Sign up to set email alerts
|

Pi-Extended Ethynyl 21,23-Dithiaporphyrins: A Synthesis and Comparative Study of Electrochemical, Optical, and Self-Assembling Properties

Abstract: 21,23-Dithiaporphyrins were synthesized containing pi-extending ethynyl substituents at the meso positions. These porphyrins displayed highly bathochromic and broadened absorbance profiles spanning 400-900 nm with molar absorptivities ranging from 2500 to 300,000 M(-1) cm(-1). Electrochemically, these ethynyl dithiaporphyrins undergo a single oxidation at 0.44 or 0.57 V and reduction at -1.17 or -1.08 V versus a ferrocene/ferrocenium internal standard depending on the type of functionalization appended to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…The silylated alkyne 2.12a (1.57 g, 57% yield) was isolated as a yellow oil. All analyses agreed with data reported in the literature …”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The silylated alkyne 2.12a (1.57 g, 57% yield) was isolated as a yellow oil. All analyses agreed with data reported in the literature …”
Section: Methodssupporting
confidence: 88%
“…All analyses agreed with data reported in the literature. 62 ((3-Fluoro-4-octylphenyl)ethynyl)trimethylsilane (2.8b). The crude mixture was purified by flash column chromatography using 100% pentane.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…However, recently Bromby et al reported a series of novel N 2 S 2 porphyrins with meso‐phenyl substituted long alkoxy groups that shows interesting optical and electrical properties and could behave as ambipolar materials for organic electronic devices [ 19–22 ] . However, to the best of our knowledge, there are only one reports of self‐assembled 21,23‐dithiaporphyrin having decyl or dodecyl chains that shows columnar liquid crystalline phases (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…[17] Nowak-Kr ol et al mentioned N 4 systems with 12 long alkyloxy groups showing low melting point and showed that the melting point of octyloxy derivative is 55.1 C that is comparable with the porphyrin 3 (54.5 C) with N 2 S 2 system reported in this article. [18] However, recently Bromby et al reported a series of novel N 2 S 2 porphyrins with meso-phenyl substituted long alkoxy groups that shows interesting optical and electrical properties and could behave as ambipolar materials for organic electronic devices [19][20][21][22] . However, to the best of our knowledge, there are only one reports of selfassembled 21,23-dithiaporphyrin having decyl or dodecyl chains that shows columnar liquid crystalline phases (Figure 2).…”
Section: Introductionmentioning
confidence: 99%